Fine mapping and molecular cloning of mutations in the herpes simplex virus DNA polymerase locus. - Coen, D M (1984)
Mutations in five phenotypically distinct mutants derived from herpes simplex virus type 1 strain KOS which lie in or near the herpes simplex virus DNA polymerase (pol) locus have been fine mapped with the aid of cloned fragments of mutant and wild-type viral DNAs to distinct restriction fragments of 1.1 kilobase pairs (kbp) or less. DNA sequences containing a mutation or mutations conferring resistance to the antiviral drugs phosphonoacetic acid, acyclovir, and arabinosyladenine of pol mutant PAAr5 have been cloned as a 27-kbp Bg+II fragment in Escherichia coli. These drug resistance markers have been mapped more finely in marker transfer experiments to a 1.1-kbp fragment (coordinates 0.427 to 0.434). In intratypic marker rescue experiments, temperature-sensitive (ts), phosphonoacetic acid resistance, and acyclovir resistance markers of pol mutant tsD9 were mapped to a 0.8-kbp fragment at the left end of the EcoRI M fragment (coordinates 0.422 to 0.427). The ts mutation of pol mutant tsC4 maps within a 0.3-kbp sequence (coordinates 0.420 to 0.422), whereas that of tsC7 lies within the 1.1-kbp fragment immediately to the left (coordinates 0.413 to 0.420). tsC4 displays the novel phenotype of hypersensitivity to phosphonoacetic acid; however, the phosphonoacetic acid hypersensitivity phenotype is almost certainly not due to the mutation(s) conferring temperature sensitivity. The ts mutation of mutant tsN20--which does not affect DNA polymerase activity--maps to a 0.5-kbp fragment at the right-hand end of the EcoRI M fragment (coordinates 0.445 to 0.448). The mapping of the mutations in these five mutants further defines the limits of the pol locus and separates mutations differentially affecting catalytic functions of the polymerase.